2013
DOI: 10.1038/leu.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

The viral oncogene Np9 acts as a critical molecular switch for co-activating β-catenin, ERK, Akt and Notch1 and promoting the growth of human leukemia stem/progenitor cells

Abstract: HERV-K (human endogenous retrovirus type K) type 1-encoded Np9 is a tumor-specific biomarker, but its oncogenic role and targets in human leukemia remain elusive. We first identified Np9 as a potent viral oncogene in human leukemia. Silencing of Np9 inhibited the growth of myeloid and lymphoblastic leukemic cells, whereas expression of Np9 significantly promoted the growth of leukemia cells in vitro and in vivo. Np9 not only activated ERK, AKT and Notch1 pathways but also upregulated β-catenin essential for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
115
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 35 publications
1
115
0
4
Order By: Relevance
“…A growing number of large-scale sequencing studies have reported detection of somatic TE insertions in some types of human cancers, and potential roles for such new insertions in malignancy are being actively investigated (49)(50)(51)(52). Other studies have investigated potential roles for human ERV-encoded proteins in cancer (53)(54)(55) or reported general transcriptional up-regulation of ERVs or L1s in various malignancies (for reviews see refs. 56 and 57).…”
Section: Activation Of Te-gene Chimeras Is Associated With Epigeneticmentioning
confidence: 99%
“…A growing number of large-scale sequencing studies have reported detection of somatic TE insertions in some types of human cancers, and potential roles for such new insertions in malignancy are being actively investigated (49)(50)(51)(52). Other studies have investigated potential roles for human ERV-encoded proteins in cancer (53)(54)(55) or reported general transcriptional up-regulation of ERVs or L1s in various malignancies (for reviews see refs. 56 and 57).…”
Section: Activation Of Te-gene Chimeras Is Associated With Epigeneticmentioning
confidence: 99%
“…In human leukemia cells, Np9 protein level is substantially higher than that in normal cells, e.g., in normal hematopoietic stem cells. Np9 may act by activating ERK, AKT and Notch1 signaling pathways and through the upregulation of b-catenin, essential for survival of leukemia stem cells [212]. Another group of researchers found that Np9 may directly interact with the RING-type E3 ubiquitin ligase LNX protein [59].…”
Section: Cancermentioning
confidence: 99%
“…HERV-K (HML-2), the youngest family of ERVs in the human genome, has been extensively investigated for potential pathogenicity and some evidence suggests that the HERV-K-encoded accessory proteins Rec and Np9 have a carcinogenic role, particularly in germ cell tumors, but also in some other cancers (26,122,123). As ongoing retrotranspositional activity of ERVs is low or nonexistent in modern humans (46), it is not surprising that no instances of activation of oncogenes via new ERV insertions have been found in human malignancy.…”
Section: Pathogenic Effects Of Ervs and Related Sequences On The Hostmentioning
confidence: 99%